2008
DOI: 10.1103/physrevlett.100.183603
|View full text |Cite
|
Sign up to set email alerts
|

Subnatural Linewidth Biphotons with Controllable Temporal Length

Abstract: This Letter describes the generation of biphotons with a temporal length that can be varied over the range of 50-900 ns, with an estimated subnatural linewidth as small as 0.75 MHz. We make use of electromagnetically induced transparency and slow light in a two-dimensional magneto-optical trap with an optical depth as high as 62. We report a sharp leading edge spike that is a Sommerfeld-Brillouin precursor, as observed at the biphoton level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
193
3
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 197 publications
(204 citation statements)
references
References 26 publications
6
193
3
2
Order By: Relevance
“…Different from previous findings [14][15][16][17][18]20,21,30], Eq. (12) clearly shows that the profile of the biphoton wave form is further manipulated by the periodic modulation of the control fields.…”
Section: Two-photon Coincidence Countscontrasting
confidence: 55%
See 1 more Smart Citation
“…Different from previous findings [14][15][16][17][18]20,21,30], Eq. (12) clearly shows that the profile of the biphoton wave form is further manipulated by the periodic modulation of the control fields.…”
Section: Two-photon Coincidence Countscontrasting
confidence: 55%
“…A recent demonstration of the generation of narrow-band biphotons in cold atomic ensembles via spontaneous four-wave mixing (SFWM) [14][15][16][17][18] has attracted considerable attention because of their long coherence time and controllable quantum wave packets. Nonlocal modulation of temporal correlation has been observed with such narrow-band biphotons [19].…”
Section: Introductionmentioning
confidence: 99%
“…In Fig. 9(b) the experimental demonstration of a near-rectangular-shape correlation is obtained at the optical depth around 53 [24]. The experimental parameters used here are γ 13 = γ 14 = 2π × 3 MHz, γ 12 = 0.02γ 13 , OD = 53, ∆ p = 48.67γ 13 , Ω p = 1.16γ 13 , and Ω c = 4.20γ 13 , respectively.…”
Section: Group Delay Regimementioning
confidence: 99%
“…Suggested by Balic et al [33] and demonstrated by Du et al [24], the group delay regime is defined as τ g > τ r and the EIT slow-light effect can be used to control the biphoton temporal coherence time. The group delay condition is equivalent to Ω e > ∆ ω g ≈ 2π/τ g , i.e., the biphoton bandwidth is determined by phase matching.…”
Section: Group Delay Regimementioning
confidence: 99%
See 1 more Smart Citation